SiO2 and TiO2 compounded oil-control repair dry water loose powder and preparation method thereof
Through the dry water loose powder combined with SiO2 and TiO2, combined with immune and microecological barrier repair agents, the shortcomings of traditional loose powder in oil control and skin barrier repair are solved, and effective repair and long-term oil control effects on sensitive skin are achieved.
Patent Information
- Application Number
- CN202411543163.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
Existing loose powder products have shortcomings in oil control, makeup maintenance and skin barrier repair, especially for sensitive skin, and have limited oil control effects for a long time.
Using SiO2 and TiO2 compound dry water loose powder, by reducing the amount of silica, increasing the content of TiO2, combined with immune barrier repair agent and microecological barrier repair agent, a stable water-in-powder structure is formed to achieve hydration and skin care, Long-term oil control and skin barrier repair.
It has achieved moisturizing and long-term oil-controlled makeup, relieves skin sensitivity, promotes the repair of the three-layer barrier, reduces makeup removal, and improves the health and stability of the skin.
Smart Images

Figure CN119385855A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cosmetics, and in particular to an oil-controlling and repairing dry water loose powder compounded with SiO2 and TiO2 and a preparation method thereof. Background Art
[0002] At present, the proportion of people with sensitive skin in my country exceeds 40% and is increasing year by year. The main cause of sensitive skin is the damage of skin barrier, including physical barrier, immune barrier and microecological barrier. After the three barriers are damaged, they affect each other and the circulation deteriorates, leading to reduced skin moisture, neurovascular hyperreactivity and immune inflammation, causing skin tightness, redness, burning, itching and stinging. Therefore, this group of people not only pay attention to the effect of makeup when applying makeup, but also hope that the makeup products will not affect skin health, and even relieve skin sensitivity, so as to achieve "makeup and care in one".
[0003] Loose powder, also known as setting powder or honey powder, is mainly applied to set makeup after using liquid foundation. It can reduce facial oiliness and prevent makeup from coming off. It also has the effect of slightly correcting color and concealing blemishes, making the skin delicate and the makeup look softer. At present, the traditional loose powder on the market is mainly talcum powder, and is mixed with silica, mica and other raw materials to form dry powder cosmetics, which has many shortcomings. First of all, due to the low water content, traditional loose powder is not only difficult to blend with the skin and easy to fall off after use, causing powder sticking and makeup coming off, but also absorbs moisture from the stratum corneum of the skin to cause dry skin, irritate sensitive skin with damaged barriers, and increase skin tightness and redness. Secondly, the ability of traditional loose powder to control oil and hold makeup for a long time is limited, and greasy and mottled phenomena will appear, because traditional loose powder only reduces facial oiliness through the physical adsorption of oil by the powder, and the powder will reach saturation after absorbing a certain amount of oil in a short period of time, and the subsequent continuous secretion of sebum will affect the makeup. Even though some traditional loose powders have added repairing active ingredients and endogenous oil-control ingredients in an attempt to improve the above-mentioned problems, the dry powder form can only carry a small amount of active ingredients. In addition, without the assistance of solvents, these active ingredients are not easily released, making it difficult to effectively repair the skin barrier and inhibit sebum secretion.
[0004] Dry water technology is to use hydrophobic powder material to wrap micron-sized water droplets to form a dry powder with a free-flowing appearance. The powder can be called dry water or powder cream. The loose powder made by dry water technology with powder wrapped in aqueous solution will release water when pressed, showing a "water-melting" phenomenon. The powder itself can absorb oil to control oil and hold makeup, while the water can make the powder more moisturized and close to the skin, improving the makeup effect. Patent CN111249200A discloses a makeup setting loose powder and its preparation method and application. The dry water technology is used to make the water content in the loose powder reach 40-75%, thereby improving the moisturizing effect and skin feel; Patent CN112402335A discloses a water-explosive loose powder and its preparation method. The dry water technology is also used to add ingredients such as aloe vera leaf extract, peony root, niacinamide, and rhodiola rosea extract to the loose powder, which has whitening and anti-aging effects. The above patents all use silica, that is, silicon dioxide as the powder wrapping material in dry water. Silica is the most commonly used raw material for preparing dry water, and it is also the raw material used in most loose powders. However, existing studies have found that silica particles can easily enter the deep part of the hair follicles, the deepest part can reach the hair bulb, and its surface hydroxyl groups can combine with oil through hydrogen bonds, have a strong interaction with the hair follicle epithelium, and accumulate in the hair follicles without falling off easily. When using products containing a large amount of silica, the silicon component is deposited too much on the skin, which hinders the normal excretion of sebum, easily blocks the hair follicles, and even causes local inflammatory reactions in the hair follicles, which is not conducive to the health of the skin barrier. At present, it has become a trend to reduce silicon substances in cosmetics, and products that do not contain or contain less silicon ingredients will be accepted by more consumers. In addition, the active ingredients used in the above patents are beneficial to the physical barrier and immune barrier, while the disorder of the microecology of the outer layer of the skin will still affect the production of ceramides and the integrity of the stratum corneum, stimulating the occurrence of immune responses. Acting only on the physical and immune barriers is not enough to improve the problem of sensitive skin. At the same time, the three layers of barriers must be repaired and the benign cycle between the barriers must be promoted to maintain the healthy and stable skin barrier; in addition, the effect of relying solely on powder to absorb oil is temporary and cannot achieve a long-term oil control effect.
[0005] Therefore, in response to the problems existing in current loose powder products, this patent hopes to compound other powder encapsulating materials to reduce silica based on the loose powder made of powder-encapsulated aqueous solution using dry water technology, and develop a loose powder that is hydrating, close to the skin, long-lasting oil control, and can repair the skin barrier and is suitable for sensitive skin. Summary of the invention
[0006] Based on the defects of the prior art, the purpose of the present invention is to provide an oil-control and repairing dry water loose powder compounded with SiO2 and TiO2 and a preparation method thereof. The oil-control and repairing dry water loose powder is compounded with other powder packaging materials to reduce the content of silicon dioxide. It is a dry water loose powder that moisturizes the skin, controls oil for a long time, can repair the skin barrier and is suitable for sensitive skin.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] In the first aspect, the present invention seeks to protect an oil-control and repairing dry water loose powder compounded with SiO2 and TiO2, the loose powder comprising the following components in parts by mass: 4-20 parts of wrapping material, 2-6 parts of moisturizer, 0.1-0.6 parts of oil-control agent, 0.55-2 parts of barrier repair agent, 0.2-0.3 parts of preservative, and 75-92 parts of water; the wrapping material comprises SiO2 and TiO2.
[0009] Preferably, in the oil control repair dry water loose powder, the content of TiO2 is 2-15 parts, and the content of SiO2 is 1-5 parts. Further preferably, the SiO2 and TiO2 are hydrophobic, and the model of SiO2 is R 812S, R 202 and R 972, wherein the type of TiO2 is TiO2T 805 and One or both of TiO2 NKT 90.
[0010] At present, the wrapping materials used in dry water technology in various fields are almost all nano-level hydrophobic SiO2. However, existing studies have found that nano-SiO2 particles can penetrate deep into the hair follicle bulb, accumulate and deposit in the hair follicle, and are not easy to remove. Therefore, there are safety risks in using them in cosmetics, which is not conducive to the health of the skin barrier. A large number of studies have confirmed that most of the nano-TiO2 particles, which are commonly used raw materials for sunscreen, are distributed in the uppermost layer of the skin stratum corneum, and a small amount stays in the upper part of the hair follicle funnel area, so they are easy to clean and remove, and are safer. The present invention uses hydrophobic TiO2 as a wrapping material to replace part of the hydrophobic SiO2, forming a stable powder-in-water structure, reducing the amount of SiO2 used, and reducing the risk of skin deposition of a large amount of SiO2. The compounding of SiO2 and TiO2 takes into account the performance of both materials, making the use of loose powder more effective. Among them, TiO2 has high whiteness, can improve skin brightness and cover minor flaws, but it absorbs little oil, and its ability to control oil and last makeup is insufficient when used alone, and the particles tend to aggregate on the skin surface; while SiO2 has a large specific surface area, strong oil absorption ability, high fluidity, and can improve the dispersion of TiO2 on the skin surface. The present invention reasonably combines the two materials within a certain content range, takes advantage of each other's strengths and weaknesses, achieves uniform dispersion, oil control and makeup lasting, and provides natural soft focus and brightening effects.
[0011] Preferably, the barrier repair agent includes an immune barrier repair agent and a microecological barrier repair agent; the immune barrier repair agent includes one or more of chamomile extract, purslane extract and scutellaria extract; the microecological barrier repair agent includes Xianting skin probiotics, Xianting ecological nutrient solution and DSM Further preferably, in terms of mass fractions, the content of the immune barrier repair agent in the oil control repair dry water loose powder is 0.05-0.5 parts, and the content of the microecological barrier repair agent is 0.5-1.5 parts.
[0012] Damage to sensitive skin barriers includes physical barriers, immune barriers and microecological barriers. Repairing the three barriers and promoting a benign cycle between the barriers can better maintain the health and stability of the skin barrier. The dry water powder contains a large amount of water and moisturizers, which can increase the moisture content of the skin, reduce the tightness of sensitive skin, and protect the integrity of the skin's physical barrier. Chamomile extract, purslane extract and scutellaria extract contain terpenes and flavonoids, which have anti-inflammatory, antioxidant and anti-allergic effects, can enhance the skin's resistance and repair the skin's immune screen. The main ingredients of Xianting Skin Probiotics are α-glucan oligosaccharides, β-oligofructose, Lactobacillus casei and Lactobacillus acidophilus, which can increase the expression of antimicrobial peptides in skin cells, promote the growth and metabolism of probiotics, and inhibit the over-proliferation of some opportunistic bacteria, increasing the diversity of microbial communities. The main ingredients of Xianting Ecological Nutrition are inulin and α-glucan oligosaccharides, which can be used by beneficial bacteria on the skin and will not be used by harmful bacteria. Through competitive inhibition of nutrition, the purpose of maintaining the structure of the skin flora is achieved. DSM The main ingredients are carbohydrate isomers, which can improve the diversity of skin flora and regulate the flora related to sensitive skin. The addition of the above ingredients enables the loose powder to promote the repair of the triple barrier, thereby alleviating skin sensitivity. In addition, the inventors have found that when the immune barrier repair agent and the microecological barrier repair agent are within the above mass fraction range, they can be completely wrapped by the wrapping material to form fine and stable powder particles.
[0013] Preferably, the oil control agent comprises one or more of pyridoxine, biotin, zinc pyrrolidone carboxylate and zinc gluconate.
[0014] Pyridoxine, also known as vitamin B6, can normalize the metabolism of amino acids, proteins and lipids in the skin, regulate the activity of sebaceous glands, and prevent various inflammations. Biotin reduces sebaceous acid levels by increasing the activity of sebaceous acid dehydrogenase, and also has an antioxidant effect. The zinc element in zinc pyrrolidone carboxylate and zinc gluconate inhibits 5α-reductase, thereby inhibiting excessive sebum secretion. The pyrrolidone carboxylic acid part can also increase the moisture content of the skin surface. These ingredients endogenously regulate sebum levels and are also beneficial for maintaining a healthy skin barrier.
[0015] Preferably, the humectant is one or more of glycerol, propylene glycol and butylene glycol.
[0016] Preferably, the preservative is one or more of phenoxyethanol, potassium sorbate, and ethylhexylglycerin.
[0017] In a second aspect, the present invention seeks to protect a method for preparing the above-mentioned oil-controlling and repairing dry water loose powder, which comprises the following steps: firstly, a barrier repair agent, an oil-control agent, a moisturizer and a preservative are added into water, and the mixture is stirred to dissolve and mix evenly to obtain an aqueous solution, and the surface tension of the aqueous solution is measured to be greater than or equal to 50 mN / m; and then the aqueous solution and the powder coating material are transferred into a blender, and stirred at 10000-20000 rpm for 20-80 seconds until a uniform powder is formed.
[0018] When the surface tension of the aqueous solution is greater than or equal to 50mN / m, the contact angle with the hydrophobic wrapping material is large, and the wrapping material will not be immersed in the aqueous solution during mixing and stirring, so as to form a structure in which the solid material wraps the aqueous solution. The preferred barrier repair agent, oil control agent, moisturizer and preservative of the present invention have no adverse effect on the surface tension of the aqueous solution, and by scientifically proportioning the above components, the surface tension of the aqueous solution is ensured to be ≥50mN / m, forming a stable dry water system while having good efficacy.
[0019] Stirring speed and time are also key factors in the formation of water structure. When the stirring speed is within the range of 10000-20000rpm and the stirring time is controlled within 20-80s, the powder formed is more stable and uniform. If the stirring speed is too low or the stirring time is too short, the coating material and the aqueous solution cannot be fully contacted and mixed; if the stirring speed is too high, the energy consumption is large and the production is difficult; and if the stirring time is too long, the material body is over-sheared, and the powder-in-water structure formed is destroyed.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention uses dry water technology to prepare a dry water loose powder in the form of water-in-powder, which has a high and stable water content, is moist and fits well, and is not prone to powder flying or sticking. In particular, SiO2 and TiO2 are compounded as the wrapping material, and the safer TiO2 replaces part of SiO2, reducing the amount of SiO2 used and reducing the risk of hair follicle deposition caused by high-content SiO2. And through the reasonable compatibility of TiO2 and SiO2, the advantages are complementary, achieving uniform dispersion, oil control and makeup holding, and providing natural soft focus and brightening effects.
[0022] (2) The loose powder provided by the present invention contains a large amount of water and moisturizer, and is combined with an immune barrier repair agent and a microecological barrier repair agent to promote the repair of the three-layer barrier and relieve skin sensitivity; the oil control agent used not only regulates oil secretion, but also helps maintain the health of the skin barrier, and combines with the powder packaging material to exogenously absorb oil, thereby achieving long-term oil control for sensitive skin and reducing makeup removal.
[0023] (3) The barrier repair agent and oil control agent of the present invention are present in an aqueous solution, wrapped by a solid material, isolated from light and oxygen, thereby largely avoiding degradation and inactivation of the active ingredients. Moreover, with the assistance of an aqueous solvent, the ingredients are quickly released and take effect quickly.
[0024] (4) The present invention also provides a method for preparing an oil-controlling and repairing dry water loose powder compounded with SiO2 and TiO2. The entire preparation process is carried out at room temperature without heating. A specific stirring speed and time are used to allow the encapsulating material and the aqueous solution to be fully mixed in a short time to obtain a loose powder with excellent appearance and good stability. The preparation method is simple, efficient, energy-saving and environmentally friendly, and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments are briefly introduced below.
[0026] Figure 1 This is the appearance of Examples 1-5 of the present invention;
[0027] Figure 2 This is the appearance of Comparative Examples 1-4 of the present invention;
[0028] Figure 3 This is the appearance of Comparative Examples 5-8 of the present invention. DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0030] The raw materials used in the examples and comparative examples of the present invention can all be obtained through conventional purchasing channels.
[0031] Examples 1-5
[0032] Examples 1-5 respectively provide an oil-controlling and repairing dry water loose powder compounded with SiO2 and TiO2, and the specific components are shown in Table 1, wherein the numbers in Table 1 represent the weight parts of each component;
[0033] Table 1: Composition of Examples 1-5
[0034]
[0035] The preparation method of Examples 1-5 is as follows: first, add glycerin, butylene glycol, phenoxyethanol, purslane extract, Cinnamomum erythrorhizome and pyridoxine into water, stir and dissolve to obtain an aqueous solution; then transfer SiO2 and TiO2 and the aqueous solution into a blender, stir at 16000 rpm for 60 seconds until a uniform powder is formed.
[0036] Comparative Examples 1-8
[0037] Comparative Examples 1-8 provide a SiO2 and TiO2 compounded oil-control and repairing dry water loose powder, respectively, and the specific components are shown in Table 2, wherein the numbers in Table 2 represent the weight parts of each component;
[0038] Table 2 Comparative Examples 1-8 Formula Components
[0039]
[0040] The difference between Comparative Example 1 and Example 1 is that the weight of the wrapping material is less than 4 parts, the weight of water is 90.95 parts, and the weight of the remaining raw materials and the preparation method are the same.
[0041] The difference between Comparative Example 2 and Example 2 is that TiO2 is not used, and an equal amount of SiO2 is used to replace TiO2, and the remaining raw material weight parts and preparation methods are the same.
[0042] The difference between Comparative Example 3 and Example 3 is that SiO2 is not used, and an equal amount of TiO2 is used to replace SiO2, and the remaining raw material weight parts and preparation methods are the same.
[0043] The difference between Comparative Example 4 and Example 3 is that the weight portion of TiO2 is higher than 15 parts, the weight portion of SiO2 is lower than 1 part, and the weight portions of other raw materials and the preparation method are the same.
[0044] The difference between Comparative Example 5 and Example 3 is that the weight parts of the wrapping material are more than 20, the weight parts of water are less than 75, and the weight parts of other raw materials and the preparation method are the same.
[0045] The difference between Comparative Example 6 and Example 5 is that the amounts of moisturizer and barrier repair agent are different and the weight portion of barrier repair agent exceeds 2 parts, and the weight portions of other raw materials and the preparation method are the same.
[0046] The difference between Comparative Example 7 and Example 2 is that the stirring speed of the stirrer is 5000 rpm, and the difference between Comparative Example 8 and Example 2 is that the stirring time is 200 s. The remaining raw material weight parts and preparation methods are the same.
[0047] Experiment 1: Appearance Observation
[0048] The appearance of Examples 1-5 and Comparative Examples 1-8 was observed and evaluated to see whether a freely flowing powder was formed, the fineness of the powder particles, and whether the liquid was completely encapsulated.
[0049] The appearance of Examples 1-5 and Comparative Examples 1-8 is shown in the attached Figure 1-3As shown. Examples 1-5 form free-flowing powders with fine powder particles and no liquid residue. Comparative Examples 1 and Comparative Examples 6-8 cannot form powders with a uniform powder-in-water structure. Comparative Example 1 presents a mixture of powder, cream and transparent liquid, indicating that the amount of encapsulating material used is too small to completely encapsulate the liquid to form a powder-in-water structure; Comparative Example 6 is in the form of lumps, because the amount of water-soluble raw material components used is too large, the surface tension of the aqueous solution is lower than 50mN / m, and the powder will be completely immersed in the aqueous solution when stirred; Comparative Example 7 has a too low stirring speed, the encapsulating material and the aqueous solution are not in contact and mixed, and the stratified state is retained; Comparative Example 8 has a large granular product due to excessive stirring time and excessive stirring shear. Comparative Examples 2-5 can form free-flowing powders, and their appearance is similar to that of Examples 1-4.
[0050] Experiment 2 Sensory Evaluation
[0051] 10 subjects were selected, and 0.02 g of the powders prepared in Examples 1-5 and Comparative Examples 2-5 were respectively applied on the inner 3×3 cm area of the arm by pressing, and the degree of moisturizing, degree of skin adhesion, and degree of uniformity were scored, and the scoring results were analyzed by t-test.
[0052] The hydration level was scored as follows: 1 point - no hydration; 2 points - slight dampness; 3 points - slightly cool to the touch, with a hydration and dampness feeling; 4 points - obviously cool to the touch and hydration; 5 points - obviously cool to the touch and hydration, with tiny drops of water observed.
[0053] The scoring criteria for skin adhesion are as follows: 1 point - the powder falls off easily, does not adhere to the skin, and has serious powder sticking; 2 points - a small amount of powder falls off, does not adhere to the skin, and has obvious powder sticking; 3 points - the powder basically adheres to the skin, with some local powder sticking; 4 points - the powder adheres to the skin, with no obvious powder sticking; 5 points - the powder adheres to the skin firmly, with no powder sticking.
[0054] The uniformity scoring criteria are as follows: 1 point - the powder is aggregated in large clumps and the color distribution is very uneven; 2 points - the powder is partially aggregated and the color distribution is uneven; 3 points - the powder is basically evenly dispersed and the color is generally uniform; 4 points - the powder is evenly dispersed, without aggregation, and the color is uniform; 5 points - the powder is easy to disperse evenly and the color is very uniform.
[0055] As shown in Table 3, the powder using the technical solution of the present invention has a higher score, a more moist skin feel, a powder that fits the skin better, a more even and natural color distribution on the skin, and better skin feel and makeup effect. Compared with Example 2, Comparative Example 2 uses only SiO2 as a wrapping material, and the degree of moisturization is lower and there is a significant difference (P < 0.01). Compared with Example 3, Comparative Example 3 completely replaces SiO2 with TiO2, and the uniformity is lower and there is a significant difference (P < 0.001). After use, the powder sticking and color mottled are particularly serious. Compared with Example 3, Comparative Example 4 has the same total weight of wrapping materials, but the weights of TiO2 and SiO2 are not within the scope of the claims, and the uniformity is also lower and there is a significant difference (P < 0.001), indicating that the ratio of a small amount of SiO2 and a large amount of TiO2 cannot effectively improve the dispersion performance of loose powder. In Comparative Example 5, too much wrapping material was used, and too little water was used. The moisturizing, skin-fitting and uniformity were not good and were significantly different from those in Example 3 (P<0.001). The powder was easy to fall off, and powder sticking and color unevenness were obvious.
[0056] Table 3 Sensory evaluation of Examples 1-5 and Comparative Examples 2-5 (n=10)
[0057]
[0058] Experiment 3: Long-lasting makeup performance test
[0059] Take a flat artificial leather, divide it into 3cm×3cm areas, and evenly apply 0.018g of the same foundation liquid in each area. Use a disposable powder puff to dip 0.02g of the powder prepared in Examples 1-3 and Comparative Examples 2-5 and spread it evenly in the area. The artificial leather is placed vertically on a table with air circulation, and the area without loose powder is used as a blank control. Use a colorimeter to test the brightness and darkness value (L value) at 0h and 8h. The larger the L value, the brighter it is, and vice versa. Calculate ΔL=L value at 0h-L value at 8h. The larger ΔL is, the greater the change in skin color from bright to dark, and the worse the makeup holding performance. Three parallel experiments were performed in each group, and the results were analyzed by t-test.
[0060] As shown in Table 4, the blank control group has the largest ΔL, and the color becomes obviously darker after 8 hours; the comparative example 2 has a larger ΔL, which is not significantly different from the control group (P>0.05). It can be seen that the powder using only SiO2 cannot maintain the bright color of the makeup for a long time, and the makeup holding performance is poor; the comparative examples 3-5 have a small ΔL and a significant difference compared with the control group. Although they perform well in maintaining the brightness of the makeup, combined with the sensory evaluation of Experiment 2, it can be seen that the skin feel and makeup effect are not good; and the test products using the technical solution of the present invention have a ΔL of less than 1.00 because SiO2 and TiO2 are compounded within a certain weight range, and the change in makeup brightness is small, which is significantly different from the control group, indicating that the technical solution of the present invention has good skin feel and makeup effect while maintaining the brightness of the makeup color within 8 hours.
[0061] Table 4 Long-lasting makeup effect of Examples 1-3 and Comparative Examples 2-5 (n=3)
[0062]
[0063] Note: * indicates P < 0.05, ** indicates P < 0.01, *** indicates P < 0.001
[0064] Experiment 4: Test of the efficacy of immune barrier repair
[0065] The neurogenic hyperreactivity of sensitive skin is usually related to the release of transient receptor potential vanilloid receptor 1 and neuropeptides. When capsaicin acts on the skin, it will activate the transient receptor potential vanilloid receptor 1 located at the end of the primary sensory neurons in the body, causing neuronal excitation and the release of related neuropeptides, which leads to redness, swelling, itching, pain, and neurogenic inflammation. In this test, the loose powder prepared in Example 1 and Example 2 was applied as a test product to the skin irritated by capsaicin, and the skin melanin hemoglobin tester Mexameter MX18 was used to detect the skin erythema value to test the immune barrier repair efficacy. The test steps are as follows:
[0066] (1) Five healthy subjects were selected. The subjects were not allowed to use skin care products on the test parts before participating in the test. Before the test, the subjects rested for 20 minutes in a laboratory with a temperature of 21±1℃ and a relative humidity of 50±5%. The test parts were exposed and placed in the test state, and they remained relaxed.
[0067] (2) Draw a 3cm×3cm experimental area on the inner side of both arms of the subject to mark the experiment. Take 20μL of the irritant (1% capsaicin in ethanol) and tap it two or three times with a finger wearing a cot in the marked box on both arms of the subject. The application area is a circular area with a diameter of 4mm, causing skin allergy. After the itching / stinging / burning sensation occurs, apply 0.02g of the test product to the irritated area respectively, and use the area without the test product as the control. The test group and the control group are randomly distributed on both arms.
[0068] (3) At 10 minutes, 20 minutes, and 30 minutes after applying the test product, the erythema value of each area was measured using the skin melanin hemoglobin tester Mexameter MX18. Compared with the control group, the smaller the percentage of the erythema value of the test product group relative to the erythema value of the area before the test, the better the effect of reducing erythema and the stronger the immune barrier repair effect. The test results were analyzed by t-test.
[0069] As shown in Table 5, the percentage of erythema value of the area using the example at each time point within 30 minutes relative to the pre-test was lower than that of the control group, and there was a significant difference with the control group. This shows that Example 1 and Example 2 can effectively alleviate the skin redness caused by irritation within 30 minutes, and the embodiment of the present invention can repair the skin immune barrier and alleviate skin sensitivity.
[0070] Table 5 Effect of reducing erythema value within 30 minutes (n=5)
[0071]
[0072] Note: * indicates P < 0.05, ** indicates P < 0.01, *** indicates P < 0.001
[0073] Experiment 5: Microecological barrier repair efficacy test
[0074] When the skin microecological barrier is damaged by external factors, one of the manifestations is a reduction in the microbial community, which cannot be restored to the original stable level. In this experiment, the loose powder prepared in Example 1 and Example 2 was used as the test product, the skin colony was collected by cotton swab wiping method, and the number of microbial colonies was determined by plate counting method. The microbial barrier repair effect was evaluated by the recovery effect of the skin microecology. The test steps are as follows:
[0075] (1) Five healthy subjects were selected. The subjects were not allowed to use skin care products on the test parts before participating in the test. Before the test, the subjects rested for 20 minutes in a laboratory with a temperature of 21±1℃ and a relative humidity of 50±5%. The test parts were exposed and placed in the test state, and they remained relaxed.
[0076] (2) Draw a 3cm×3cm experimental area on the inner side of both arms of the subject to mark the experiment. After wiping each area 50 times with a sterile cotton swab dipped in a small amount of physiological saline, soak the cotton swab in 4mL of physiological saline and oscillate it with a vortex oscillator to obtain the bacterial solution sample to be tested. The plate count method is used to determine the sample to be tested, which is used as the initial colony count of the skin and is recorded as A0. After wiping, 0.02g of the test product is applied to the test area, and the area without the test product is used as the control. The test group and the control group are randomly distributed on both arms. After 4h and 8h, the same method is used to sample and count the corresponding areas, which is used as the recovery value of the skin colony count and is recorded as A1.
[0077] (3) Calculation of results: Recovery rate of skin colonies (%) = [(A1-A0) / A0] × 100
[0078] As shown in Table 6, the skin colony recovery rates of Example 1 and Example 2 after 4 hours and 8 hours were higher than those of the control group, and there was a significant difference from the control group. The embodiment of the present invention is conducive to the recovery of skin microbial flora, repairing damaged skin microecological barriers, and alleviating skin sensitivity.
[0079] Table 6 Skin colony recovery rate within 8 hours (n=5)
[0080]
[0081] Note: * indicates P < 0.05, ** indicates P < 0.01, *** indicates P < 0.001
[0082] The above is only a preferred embodiment of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of this application.
Claims
1. An oil-controlling and repairing dry water loose powder compounded with SiO2 and TiO2, characterized in that: The loose powder comprises the following components in parts by mass: 4-20 parts of wrapping material, 2-6 parts of moisturizing agent, 0.1-0.6 parts of oil control agent, 0.55-2 parts of barrier repair agent, 0.2-0.3 parts of preservative, and 75-92 parts of water; the wrapping material comprises SiO2 and TiO2.
2. The oil-controlling and repairing dry water loose powder according to claim 1, characterized in that: Calculated by weight, the content of TiO2 in the oil-controlling and repairing dry water loose powder is 2-15 parts, and the content of SiO2 is 1-5 parts.
3. The oil-controlling and repairing dry water loose powder according to claim 1 or 2, characterized in that: The SiO2 and TiO2 are hydrophobic, and the type of the SiO2 is R 812S, R 202 and R972, the type of TiO2 is TiO2T 805 and One or both of TiO2NKT 90.
4. The oil-controlling and repairing dry water loose powder according to claim 1, characterized in that: The barrier repair agent includes an immune barrier repair agent and a microecological barrier repair agent; the immune barrier repair agent includes one or more of chamomile extract, purslane extract and scutellaria extract; the microecological barrier repair agent includes Xianting skin probiotics, Xianting ecological nutrient solution and DSM One or more of .
5. The oil-controlling and repairing dry water loose powder according to claim 4, characterized in that: Calculated by weight, the content of the immune barrier repair agent in the oil-control repair dry water loose powder is 0.05-0.5 parts, and the content of the microecological barrier repair agent is 0.5-1.5 parts.
6. The oil-controlling and repairing dry water loose powder according to claim 1, characterized in that: The oil control agent includes one or more of pyridoxine, biotin, zinc pyrrolidone carboxylate and zinc gluconate.
7. The oil-controlling and repairing dry water loose powder according to claim 1, characterized in that: The moisturizing agent includes one or more of glycerin, propylene glycol and butylene glycol.
8. The oil-controlling and repairing dry water loose powder according to claim 1, characterized in that: The preservatives include one or more of phenoxyethanol, potassium sorbate and ethylhexylglycerin.
9. The method for preparing the oil-controlling and repairing dry water loose powder according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: firstly, adding a barrier repair agent, an oil control agent, a moisturizer and a preservative into water, stirring and dissolving them to obtain an aqueous solution, and measuring the surface tension of the aqueous solution to be greater than or equal to 50 mN / m; then transferring the aqueous solution and the powder coating material into a mixer, stirring for 20 to 80 seconds at 10,000 to 20,000 rpm until a uniform powder is formed.
Citation Information
Patent Citations
Setting loose powder as well as preparation method and application thereof
CN111249200A